Academic literacies: the word is not enough. Issue 2 (17th February 2018) - Richards, Kendall; Pilcher, Nick
ABSTRACT: For Academic Literacies, the world is textually mediated; written texts and what informs them reveal elements such as subject-discipline practices. Furthermore, multi-modalities, for example, visual representation, inform written text, and multiple methods of inquiry, including interviews, shed light on written text production. In this article we argue that the word is not enough, and non-textual elements must also be considered. From multiple-discipline focused research, we present data from interviews and focus groups with Design and Nursing lecturers that explored student success holistically, not solely through, or for, written text production. We highlight non-textual elements key to both student success, and written text production, such as 'empathy', the 'visual', the 'non-verbal', and also the inability of text to reveal certain key features. We argue that rather than solely prioritise text, Academic Literacies approaches can more effectively help students succeed by holistically considering non-textual elements.